Book Review - Alicja Staniszewska (Suomen Antropologi)
Book Review: Venkatesan, Soumhya. Decolonizing Anthropology: An Introduction. Cambridge: Polity. 2025. 252 pp. ISBN: 9781509540600 (softcover), 9781509540594 (hardcover); 9781509540617 (e-book).